2011
DOI: 10.1177/0022034511414156
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Hematopoietic Stem Cell Transplantation and Hyposalivation

Abstract: Hyposalivation is a common adverse effect of anti-neoplastic therapy of head and neck cancer, causing impaired quality of life and predisposition to oral infections. However, data on the effects of hematopoietic stem cell transplantation (HSCT) on salivary secretion are scarce. The present study determined stimulated whole-saliva flow rates in HSCT recipients in comparison with a healthy control group. Stimulated whole-saliva flow rates of 228 allogeneic HSCT recipients (134 males, 94 females; mean age, 43 yrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 24 publications
9
36
2
3
Order By: Relevance
“…[31][32][33] However, as observed in our previous study, even lower radiation doses (6 Â 2 Gy) used as conditioning therapy before HSCT may contribute to hyposalivation. 9 Comparable complications caused by TBI have been reported in other studies among adults and children. [34][35][36] In the current study, the observed hyposalivation may partly be due to permanent destruction and dysfunction of the glandular tissue caused by non-fractionated TBI, as 89% of the recipients had received such treatment.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…[31][32][33] However, as observed in our previous study, even lower radiation doses (6 Â 2 Gy) used as conditioning therapy before HSCT may contribute to hyposalivation. 9 Comparable complications caused by TBI have been reported in other studies among adults and children. [34][35][36] In the current study, the observed hyposalivation may partly be due to permanent destruction and dysfunction of the glandular tissue caused by non-fractionated TBI, as 89% of the recipients had received such treatment.…”
Section: Discussionmentioning
confidence: 66%
“…8,30 In HSCT-treated patients, radiotherapy is likely to be one etiological factor for hyposalivation. 9 Hypofunction of salivary glands depends on the cumulative dose to the gland tissue, and exposure to high total radiation doses (426-36 Gy) leads to a significant reduction of salivary secretion. [31][32][33] However, as observed in our previous study, even lower radiation doses (6 Â 2 Gy) used as conditioning therapy before HSCT may contribute to hyposalivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with salivary gland cGvHD are at risk of developing complications because of diminished salivary defense mechanisms, including antifungal and anticariogenic activities [88, 89]. Castellarin and coworkers reported cGvHD-associated rapidly progressive dental caries with cervical and interproximal involvement [90].…”
Section: Graft Versus Host Diseasementioning
confidence: 99%
“…As alterações radiográficas mais frequentes são microdontia generalizada, ausência de dentes por extrações e agenesias, transposições e supranumerários (ACIKGOZ et al, 2005;DE ARAUJO et al, 2007;TEKCICEK et al, 2007;DE ARAUJO et al, 2011;SHETTY et al, 2011 (STOOPLER et al, 2007;ISLAM et al, 2011). Na literatura investigada, as alterações estomatológicas mais frequentes nos pacientes em preparo para TCTH foram gengivite, acúmulo de biofilme, cálculo dentário, periodontite com bolsas profundas e perda significativa de osso alveolar, alto índice de cárie, redução de fluxo salivar, restaurações com infiltrações necessitando de retratamento, lesões periapicais, raízes residuais, dentes parcialmente irrompidos, mucosite, dor relacionada à articulação têmporo-mandibular, infecções oportunistas por fungos e vírus, infiltrado leucêmico gengival, petéquias, equimoses, língua saburrosa, úlceras traumáticas infectadas, erosão dental, hiperplasia ou hipertrofia gengival, alterações oclusais e na formação dos dentes após quimioterapia na infância (LUCAS et al, 1998;GRABER et al, 2001;MELKOS et al, 2003;VAUGHAN et al, 2005b;YAMAGATA et al, 2006;BRENNAN et al, 2008;DA SILVA SANTOS et al, 2008;DUREY et al, 2009;BOER et al, 2010;HONG et al, 2010;LAAKSONEN et al, 2011;PALMASON et al, 2011;GURGAN et al, 2012;HERNANDEZ-FERNANDEZ et al, 2012). A variedade de manifestações em diversos graus de intensidade é resultado do tempo variado entre o adoecimento e o momento do diagnóstico.…”
Section: Doenças Onco-hematológicasunclassified